2019
DOI: 10.1128/mbio.02624-18
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine Is a Siderophore-Like Iron Chelator That Promotes Salmonella enterica Serovar Typhimurium Virulence in Mice

Abstract: We have recently shown that the catecholamine dopamine regulates cellular iron homeostasis in macrophages. As iron is an essential nutrient for microbes, and intracellular iron availability affects the growth of intracellular bacteria, we studied whether dopamine administration impacts the course of Salmonella infections. Dopamine was found to promote the growth of Salmonella both in culture and within bone marrow-derived macrophages, which was dependent on increased bacterial iron acquisition. Dopamine admini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 56 publications
3
40
0
Order By: Relevance
“…RNA extraction, cDNA transcription and quantitative RT-PCR was performed exactly as described previously [47]. cDNA levels of the respective genes were calculated as relative expression to the house keeping gene beta-Glucuronidase (Gusbeta).…”
Section: Methodsmentioning
confidence: 99%
“…RNA extraction, cDNA transcription and quantitative RT-PCR was performed exactly as described previously [47]. cDNA levels of the respective genes were calculated as relative expression to the house keeping gene beta-Glucuronidase (Gusbeta).…”
Section: Methodsmentioning
confidence: 99%
“…Low iron diet had an iron content of ≤9 mg iron/kg diet (26), high ion diet contained 5 g iron/kg diet (both diets from Altromin). Male mice were used at 8-12 weeks of age and infected intraperitoneally with 500 CFU of S. Typhimurium in 200 ml PBS (27)(28)(29). After 14 days of infection mice were euthanized by cervical dislocation, spleens and livers were isolated, erythrocytes lysed, and flow cytometry was performed.…”
Section: Infection Of Micementioning
confidence: 99%
“…These biomolecules play a key role in energy metabolism and immune tolerance of gut microbes by upregulating IL-10 ( 77 , 78 ). Interestingly, microbial DA and NE were demonstrated to influence iron absorption and metabolism by functioning as siderophores or bacterial iron scavengers ( 79 , 80 ). Interestingly, a recent study found that enterobactin, an Escherichia coli siderophore, can be transferred to the host, revealing a novel form of inter-kingdom communication ( 81 ).…”
Section: Psychotropic Drugs and Obesitymentioning
confidence: 99%